2021
DOI: 10.1038/s41598-021-83705-z
|View full text |Cite
|
Sign up to set email alerts
|

Inverse relation between structural flexibility and IgE reactivity of Cor a 1 hazelnut allergens

Abstract: A major proportion of allergic reactions to hazelnuts (Corylus avellana) are caused by immunologic cross-reactivity of IgE antibodies to pathogenesis-related class 10 (PR-10) proteins. Intriguingly, the four known isoforms of the hazelnut PR-10 allergen Cor a 1, denoted as Cor a 1.0401–Cor a 1.0404, share sequence identities exceeding 97% but possess different immunologic properties. In this work we describe the NMR solution structures of these proteins and provide an in-depth study of their biophysical proper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 74 publications
1
13
0
Order By: Relevance
“…Moreover, NMR RD experiments show that this segment is rigid and structurally homogeneous in solution (Supporting Information Figure S7), irrespective of whether the internal cavity is loaded with the ligand cargo or not. This is noteworthy in light of a recent study of the major hazelnut allergens Cor a 1.04, which revealed that antibody IgE binding and structural flexibility of these PR-10 proteins are correlated . Structural flexibility might represent a critical determinant that relates ligand binding of PR-10 allergens to immunologic reactions …”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, NMR RD experiments show that this segment is rigid and structurally homogeneous in solution (Supporting Information Figure S7), irrespective of whether the internal cavity is loaded with the ligand cargo or not. This is noteworthy in light of a recent study of the major hazelnut allergens Cor a 1.04, which revealed that antibody IgE binding and structural flexibility of these PR-10 proteins are correlated . Structural flexibility might represent a critical determinant that relates ligand binding of PR-10 allergens to immunologic reactions …”
Section: Resultsmentioning
confidence: 89%
“…This is noteworthy in light of a recent study of the major hazelnut allergens Cor a 1.04, which revealed that antibody IgE binding and structural flexibility of these PR-10 proteins are correlated. 50 Structural flexibility might represent a critical determinant that relates ligand binding of PR-10 allergens to immunologic reactions. 51 …”
Section: Resultsmentioning
confidence: 99%
“…RD data contain quantitative information about the structural flexibility that occurs on the millisecond timescale on a per-residue basis [ 29 ]. As noted previously for PR-10 allergens from birch pollen and hazelnut, these proteins are remarkably flexible, with a significant portion of the backbone amides showing nonflat relaxation-dispersion curves [ 21 , 22 ]. Figure 3 A compares the backbone amide 15 N relaxation-dispersion amplitudes (ΔR 2,eff values) of the thirteen PR-10 proteins in this study, in detail.…”
Section: Resultsmentioning
confidence: 90%
“…The biophysical research on PR-10 allergens in the last decades has focused on ligand binding and structure elucidation by NMR spectroscopy or X-ray crystallography, and on understanding how the structural properties of these proteins are related to the observed allergenic behavior [ 16 ]. Only a few studies have addressed the structural flexibility of these proteins, which is a feature that may be related to the affinity of low-molecular-weight ligands binding to the internal cavity, and IgE binding to the outer surfaces of these proteins [ 21 , 22 , 23 , 24 ]. In this work, we provide a thorough and quantitative comparison of the structural flexibilities of 12 PR-10 food allergens from apple, hazelnut, peach, kiwi, peanut, and plum, along with—and in comparison to—the sensitizing birch-pollen allergen, as observed by solution NMR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic protein structures may be important for an optimal configuration of epitope residues and the Fc RI cross-linkage [75,76]. Recently, a study of the hazelnut allergen Cor a 1.04 isoforms reported an inverse relation between the conformational flexibility and IgE binding [77]. The IgE reactivity correlated with the rigidification of the protein backbone, where the highest IgE binding was observed for Cor a 1.0401, with the most rigid backbone scaffold, whereas the lowest IgE binding potential was determined for the most structurally flexible isoform Cor a 1.0404.…”
Section: Effect Of Ligand Binding On the Allergenicity Of The Proteinmentioning
confidence: 99%